2001
DOI: 10.1029/2000gl003795
|View full text |Cite
|
Sign up to set email alerts
|

Interrelation between ELF transients and ionospheric disturbances in association with sprites and elves

Abstract: C), whereas a large lightning peak current (+223-+470 kA) (or slow-tail amplitude) leading to the strong EMP is necessary to initiate elves, but with rather small ionospheric disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
101
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 17 publications
9
101
0
Order By: Relevance
“…The only papers published on elve-related VLF perturbations so far are those of Hobara et al (2001Hobara et al ( , 2003 and Mika et al (2005). Hobara et al (2001Hobara et al ( , 2003 reported perturbations in association with 7 elves out of a total of 17.…”
Section: Electron Density Changes Induced By the Lightning Emp In Thementioning
confidence: 99%
See 1 more Smart Citation
“…The only papers published on elve-related VLF perturbations so far are those of Hobara et al (2001Hobara et al ( , 2003 and Mika et al (2005). Hobara et al (2001Hobara et al ( , 2003 reported perturbations in association with 7 elves out of a total of 17.…”
Section: Electron Density Changes Induced By the Lightning Emp In Thementioning
confidence: 99%
“…Hobara et al (2001Hobara et al ( , 2003 reported perturbations in association with 7 elves out of a total of 17. However, there is some doubt if these perturbations were indeed caused by ionisation changes relating to elves.…”
Section: Electron Density Changes Induced By the Lightning Emp In Thementioning
confidence: 99%
“…The perturbation of ionospheric and mesospheric conductivity due to the sprite ionization column and sprite halos has been observed by measuring changes in the amplitude and phase of signals from distant narrowband VLF transmitters passing over a thunderstorm region (Dowden et al, 1994;Inan et al, 1995Inan et al, , 1996aInan et al, , b, 1997Inan et al, , 2010Molchanov et al, 1998;Hobara et al, 2001;Otsuyama et al, 2004;Neubert et al, 2008). The perturbations of VLF transmitter signals have been observed a few ms after the causative lightning stroke.…”
Section: Vlf and Elf Phenomena Associated With Spritesmentioning
confidence: 99%
“…The first peak corresponds to the causative lightning, whereas the second peak was found to be simultaneous in time with sprite luminosity and it appears to be proportional in amplitude to the brightness of the sprite. Based on the ELF field measurements, the charge moment change of the sprite can be extracted (Boccippio et al, 1995;Hobara et al, 2001Hobara et al, , 2006Hayakawa et al, 2004;Matsudo et al, 2009). In several cases the sprite current moments responsible for the ELF pulse were estimated to be of several hundred kA km (Cummer et al, 1998(Cummer et al, , 2006a.…”
Section: Vlf and Elf Phenomena Associated With Spritesmentioning
confidence: 99%
“…The absence of observed optical phenomena (mesospheric optical emissions such as sprites) in the Hokuriku area (Sea of Japan side) indicates that the period was not extremely active in lightning as compared with the previous winter [Hobara et al, 2001]. Based on VLF subionospheric observation at Moshiri (Hokkaido) and Maizuru (near Kyoto) for two VLF transmitter signals (NWC (Australia) and NPM (Hawaii)), we have found the following; (1) Lightning discharges are found not only on the JapanSea side, but also on the Pacific side.…”
mentioning
confidence: 99%